Legal Readiness Of Agreements Facing The Digitalization Era Banking In Islamic Banking Financing Transactions - Utary Maharany Barus; T. Keizeirina Devi Azwar; Cheryl Patriana Yuswar; Siti Nurahmi Nasution; Hilbertus Sumplisius M. Wau (Journal Of Social Science (JoSS), 2023)
Digital developments in the banking system occur not only in conventional banks but also in Islamic banks. The digitalization of Islamic financing transactions is also inseparable from technological developments, especially in the use of electronic contracts. Sharia banks implementation of sharia business activities is regulated in the “Compilation of Sharia Economic Law” (KHES). Electronic Contracts are one of the innovations related to commercial life while navigating the legality of making agreements, even though digitally included by Islamic Banks, thus raising questions about the validity and risks of these electronic contracts. Competence, legal relations, objects, free consent, and jurisdiction are indicators of readiness for treaty legal instruments in the development of the current digitalization era. This study examines the legal readiness of agreements facing the era of digitalization of Islamic banking in financing transactions. This study uses an empirical method to examine the provisions of laws and regulations in detail. This was a normative juridical study. The results of the field study show that the electronic contracts implemented by Bank Mega Syariah and Bank Muamalat through e-contracts meet the legal provisions of the agreements stipulated in positive law in Indonesia. The results of the literature study also show that treaty legal instruments as stipulated in BW, Law 11/2008 juncto PP 71/2019 and KHES have accommodated the development of electronic agreement legal needs as an implication of the digitalization era in banking financing transactions.